The Effect of Carrot Flour Substitution and Vacuum Frying Time on Characteristics of Carrot Simulation Chips - Rosida, Rosida; Purwanti, I. I. (Fakultas Teknologi Pertanian Universitas Brawijaya, 2008)
The making of carrot simulation chips had been studied. The carrot simulation chips were made from carrot flour and tapioca flour and used vacuum frying process. The vacuum frying process was used in order to maintain color and nutritional component of carrot. Therefore it did not undergo many changes due to lower temperature and time of frying process.Â The aim of this research was to determine the best treatment (substitution level of carrot flour to tapioca flour, and vacuum frying time) to produce simulation chips which had good qualities and preferred by the panels. This research used Completely Randomized Design with factorial pattern which contained 2 factors; the first factor was substitution degree of carrot flour to tapioca flour (10%, 20%, 30%) and the second factor was vacuum frying time (2, 4, 6 minutes).It was found that the best treatment was 10% substitution of carrot flour and 6 minutes frying times. It produced carrot simulation chips which had 2,89% moisture content, 74,98% starch content, 5,19 ïg/100g ï¢-carotene content, 48,25% yield, and 180,67% expansion volume.Keywords : carrot simulation chips, carrot flour, tapioca flour, vacuum frying time